Do older patients receive adequate stroke care? An experience of a neurovascular clinic. Issue 1001 (7th April 2009) - Kee, Y-Y K; Brooks, W; Bhalla, A
Abstract : Background: National guidelines and government directives have adopted policies for urgent assessment of patients with a transient ischaemic attack or minor stroke not admitted to hospital. The risk of recurrent stroke increases substantially with age, as does the potential benefit of secondary prevention. In order to develop effective strategies for older patients, it is important to identify how stroke care is currently provided for this patient group. Methods: Between 2004 and 2006, older patients (>75 years) referred to a neurovascular clinic were compared with younger patients (⩽75 years). Sociodemographic details, clinical features, resource use and secondary prevention in a neurovascular clinic were collected. Results: Of 379 patients referred to the clinic, 129 (34%) were given a non-stroke diagnosis. Of the remaining 250 patients, 149 (60%) were ⩽75 years. Median time from symptom onset to clinic appointment was similar for the two groups (24 (IQR 15–42) vs 24 (IQR 14–43) days; p = 0.58). Older patients were more likely to be in atrial fibrillation (10.1% vs 22.8%, p<0.001) and have lacunar stroke (34.7% vs 22.1%; p = 0.04). CT rates were similar in the two groups (27.8% vs 80.0%, p = 0.75). Scans were performed more quickly in younger patients (p<0.01). MRI scan rates were higher in younger patients (26% vs 4%, p<0.01), as was carotid Doppler imaging (92% vs 77%, p<0.01). There were no differences in prescribed secondary preventive treatments. Older patients experienced less delay for carotid endarterectomy (49 vs 90 days, p<0.01). Younger patients were more likely to be given advice on weight reduction (30.2% vs 12.9%, p<0.01) and diet (46.3% vs 31.7%, p = 0.02) than older patients. Conclusions: Older patients were less likely to receive diagnostic investigations and lifestyle modification advice than younger patients. Guidelines need to be adopted to ensure prompt evidence-based stroke care in the outpatient setting.